Weldability of duplex stainless steel - Pramanik, Alokesh; Littlefair, G.; Basak, A. (Taylor and Francis Inc., 2015)
Duplex stainless steels (DSSs) have many advantages due to the unique structural combination of ferrite and austenite grains. The structural change of these materials is very complex during welding, and it deteriorates the functional properties. This research investigates different welding processes such as laser beam, resistance, tungsten inert gas, friction stir, submerged arc, and plasma arc weldings considering the research available in the literature. The welding mechanism, change of material structure, and control parameters have been analyzed for every welding process. This analysis clearly shows that DSS melts in all most all welding processes, but the thermal cycle and maximum heat input are different. This difference affects the resulting structure and functional properties of the weld significantly.